Comparing road and rail investment in cost-benefit analysis - Tom Worsley (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2020)
This paper examines whether the results of cost-benefit analyses (CBA) for road and rail projects can be compared with each other. Road and rail projects address different transport needs and aim to solve different problems. This does not make comparisons between CBAs for each mode impossible, but requires a nuanced approach.
Keywords: 330